Dok3–protein phosphatase 1 interaction attenuates Card9 signaling and neutrophil-dependent antifungal immunity - Loh, Jia Tong (2019)
Invasive fungal infection is a serious health threat with high morbidity and mortality. Current antifungal drugs only demonstrate partial success in improving prognosis. Furthermore, mechanisms regulating host defense against fungal pathogens remain elusive. Here, we report that the downstream of kinase 3 (Dok3) adaptor negatively regulates antifungal immunity in neutrophils. Our data revealed that Dok3 deficiency increased phagocytosis, proinflammatory cytokine production, and netosis in neutrophils, thereby enhancing mutant mouse survival against systemic infection with a lethal dose of the pathogenic fungus Candida albicans. Biochemically, Dok3 recruited protein phosphatase 1 (PP1) to dephosphorylate Card9, an essential player in innate antifungal defense, to dampen downstream NF-κB and JNK activation and immune responses. Thus, Dok3 suppresses Card9 signaling, and disrupting Dok3-Card9 interaction or inhibiting PP1 activity represents therapeutic opportunities to develop drugs to combat candidaemia.